Household Stockholding Behavior During the Great Financial Crisis - Jie Zhou (Bank of Canada, 2015)
Using the Panel Study of Income Dynamics, this paper studies household stock market participation and trading behavior in 2007 - 09, a period that saw a major stock market downswing. The stock market participation rate fell after the market crash. We find evidence that less-educated households, poor households and households with heads belonging to a minority are the ones that dropped out of the market after the market crash. We also find that, of the households that held stocks in non-retirement accounts in 2007, a significant portion reported no stock market activity in non-retirement accounts during the crisis period.
Keywords: G01; G11; 330; Asset pricing; Financial markets